2007
DOI: 10.1111/j.1467-9299.2007.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Service Motives on Work Outcomes in Australia: A Comparative Multi‐dimensional Analysis

Abstract: There is a general consensus that individuals who are driven to serve the public interest can possess a mix of public service motives for engaging in altruistic actions. This article proposes that when analysed simultaneously, some public service motives may play a more important role than others in influencing work outcomes. The pressing questions are which ones and how? Through a survey of a group of Australian public sector employees, this article explores the relationship between the various dimensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
153
1
21

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(189 citation statements)
references
References 64 publications
11
153
1
21
Order By: Relevance
“…Studies conducted by several scholars in South Korea also confirmed the study of American and European scholars (Choi, 2001;Kim, 2006;Kim, 2009). In Australia, the study of Taylor (2007; also proved the same conclusions. In addition, the study conducted by Liu et al (2008), ), Liu et al (2014 showed similar findings.…”
Section: Introductionsupporting
confidence: 67%
“…Studies conducted by several scholars in South Korea also confirmed the study of American and European scholars (Choi, 2001;Kim, 2006;Kim, 2009). In Australia, the study of Taylor (2007; also proved the same conclusions. In addition, the study conducted by Liu et al (2008), ), Liu et al (2014 showed similar findings.…”
Section: Introductionsupporting
confidence: 67%
“…In particular, the items of the dimension of attraction to policy making lack face and content validity (Camilleri 2006;Coursey and Pandey 2007;Coursey et al 2008;Kim 2009b;Ritz 2011). Others have suggested that commitment to public interest dimension needs to concentrate more on a personal disposition to pursue public values (Castaing 2006;Leisink and Steijn 2009;Taylor 2007), and the items of compassion do not always represent affective motives (DeHart-Davis, Marlowe, and Pandey 2006;Moynihan and Pandey 2007;Wright 2008).…”
Section: Refining the Multidimensional Psm Frameworkmentioning
confidence: 99%
“…Only when the common elements of PSM are identified, and a reliable way of measuring them is developed, can scholars begin to understand the differences in PSM across cultures including the possibility of additional culturally specific dimensions. Although some important steps have been taken to internationalize the PSM scale (Kim 2009a;Taylor 2007;Vandenabeele 2008b), to date this work has been done incrementally, one country at a time. This study, however, takes a more systematic and comprehensive approach by combining the efforts of international PSM scholars to develop and then test a revised measurement instrument for PSM in 12 countries.…”
Section: Measuring Psm and The Globalization Of Psm Researchmentioning
confidence: 99%
See 2 more Smart Citations